(untitled) (Research, Society and Development, 2021)
The intense rainfall is characterized by its peculiarly irregular temporal and spatial distribution. A maximum recorded during a 24-hour interval starting at any time will be set to a 24-hour maximum. It should not be confused with the 1-day classification which refers to the maximum classification observed in 1 day, always collected at the same time, considered here from 9:00 am to 9:00 am the following day. The objective of this work is to determine intense rainfall disaggregation constants for the state of Bahia from 19 historical rainfall series, comparing them with the coefficients obtained for other regions of Brazil. For modeling the frequency of heavy rains of different durations, the probability distribution was used. To determine the disaggregation constants, the duration relations method is used. This method consists of two aspects: a) the tendency of the probability curves of different durations to remain parallel to each other; and b) for different locations, there is a great similarity in the relationships between maximum mean precipitations of relationships. The following mean disaggregation constants for the state of Bahia were selected: h10min/h30min = 0.48; h20min/h30min = 0.79; h30min/h1h = 0.74; h40min/h1h = 0.87; h50min/h1h = 0.94; h1h/h24h = 0.59; h2h/h24h = 0.69; h3h/h24h = 0.76; h4h/h24h = 0.80; h6h/h24h = 0.85 e h12h/h24h = 0.92. Such constants are an important tool for applications that demand the estimation of intense rains of duration in the state of Bahia.